Impact of climate changes in Europe on European pollution levels - Zlatev, Z. (Інститут програмних систем НАН України, 2006)
Changes in climate variability and extreme weather and climate events in the 20th century, especially in the last two-three decades of the 20th century, have been discussed in many recent scientific publications. Attempts to project the results of such studies in the future have been made under different assumptions. The following two topics are discussed: · of the well-known scenarios predicting changes of the climate in the 21st century (taken from Houghton et al., 2001) and · the impact of these changes on the pollution levels in different parts of Europe.